The Simulated Classroom Biology—A simulated classroom environment for capturing the action‐oriented professional knowledge of pre‐service teachers about evolution. (8th August 2022) - Fischer, Julian; Machts, Nils; Bruckermann, Till; Möller, Jens; Harms, Ute
Abstract: Background: The professional knowledge of pre‐service teachers is highly important for effective and successful teaching. In recent years, many research groups have been engaged in developing simulated classroom environments to capture especially the pedagogical knowledge (PK) of pre‐service teachers, neglecting the content‐related facets of professional knowledge such as pedagogical content knowledge (PCK). Objectives: In the present study, we describe the development of a simulated classroom environment—the Simulated Classroom Biology (SCR Bio )—and provide evidence regarding its validity to assess pre‐service biology teachers' action‐oriented PCK in the area of evolution. Methods: This study examined the evidence supporting the validity of using the SCR Bio to investigate action‐oriented PCK of pre‐service biology teachers. The (1) evidence based on test content (expert ratings) and the (2) evidence based on relation to other variables (known‐groups comparison) was obtained. We tested the SCR Bio with N  = 76 German pre‐service biology teachers. Results and Conclusions: Our results show the successfully operationalized PCK in the SCR Bio through explicit allocation of specific misconceptions to each virtual student's answer and the valid measurement of pre‐service biology teachers' action‐oriented PCK. This results in a validated simulated classroom environment for pre‐service but also in‐service teachers. In the future, the SCR Bio will be developed from an assessment instrument to a training tool to simulate explicit teaching situations. This allows to complement the predominantly theoretical components of university‐based teacher education with practice‐based simulated classroom environments. Lay Description: What is already known about this topic: The professional knowledge of pre‐service teachers is a prerequisite for quality teaching in the future, as well as student achievement. Simulated classroom environments are already being used, primarily to examine and train the pedagogical knowledge of pre‐service teachers. The action‐oriented character of simulated classroom environments can bridge the theory‐practice gap of university‐based education programs. What this paper adds: Description of an innovative simulated classroom environment—the Simulated Classroom Biology. Ability to capture several domains of professional knowledge in an action‐oriented setting. Validation of the Simulated Classroom Biology using various validity aspects. Implications of study findings for practitioners. Description of validation steps for developing simulated classroom environments. A validated simulated classroom environment is provided to capture various knowledge domains of professional knowledge in an actionable setting. The Simulated Classroom Biology can be adapted to new subjects and teaching topics by changing the content.